IMPLEMENTASI PEMBELAJARAN IBADAH SALAT DENGAN MODEL E-LEARNING DI SDN PEJATEN TIMUR MASA PANDEMI COVID 19 - Kusdarwati, Kusdarwati; Bariyah, Oneng Nurul (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
This study aims to enlighten the implementation of the teaching of Islamic Prayers (Salat) procedures and its supplications and to analyze the inhibiting and supporting factors in the implementation of e-learning in improving the ability of students to perform Islamic Prayers (Salat), during the covid-19 pandemic. It is a class action research (Classroom Action Research) which is carried out through 3 cycles. Each cycle consists of planning, action, observation and reflection. The research subjects were 30 class II students at SDN Pejaten Timur 07 in the second semester of 2020-2021. Research data obtained through observation, tests, and documentation, using qualitative descriptive analysis techniques. The result of the study shows that e-learning method can improve the students ability in performing the daily prayers, if students have a disciplined attitude in participating in the e-learning, have a high sense of responsibility, active in using the e-learning applications until the learning process is complete, cooperative and honest. The inhibiting factors in the learning process includes technological problems such as the disconnection of the internet network during learning, parents who are not always able to accompany their children during the learning process for reasons of work and others. Whereas the supporting factors in implementing learning using the e-learning method includes providing continuous motivation in fostering student’s interest in learning in order to increase enthusiasm in memorizing prayer supplications, using appropriate learning media, sufficient internet quota, as well as the level of education of the parents.